APPLICATION OF THE PRINCIPLE OF NOTARY ACCURACY AS AN EFFORT TO AVOID THE PRACTICE OF MAKING NOMINEE AGREEMENTS RELATED TO THE TRANSFER OF LAND OWNERSHIP TO FOREIGN CITIZENS - Tiara, Elfira Dela; Abubakar, Lastuti; Baraba, Badar (EKSEKUSI, 2023)
This research aims to examine the implementation of the principle of notary accuracy as an effort to avoid the practice of making nominee agreements regarding the transfer of land ownership rights to foreign citizens along with the legal consequences for notaries who ignore the principle of equality with those making deeds based on these agreements.The research method used is normative juridical by examining library materials or secondary data, including legal principles, legal systematics, research on levels of vertical and horizontal synchronization, and legal comparisons. This research uses an applicable legislative approach linked to legal theories and practices relating to legal issues with analytical descriptive research specifications and qualitative juridical data analysis methods.Based on the results of the research, it can be concluded that the refusal to make a deed based on a nominee agreement regarding the transfer of ownership rights to land to a foreign citizen is part of the implementation of the principle of notarial accuracy considering that the deed violates the objective requirements in the form of a halal cause in the terms of the validity of the agreement in Article 1320 of the Civil Code and results in a deed declared null and void by law. Cancellation of an act of nominee agreement provides a legal basis for imposing civil sanctions on the Notary, which may include payment of fees, compensation and interest. By considering the impact, Notaries should carry out their duties carefully, professionally, prioritizing integrity and good morals.